Knowledge of Folic Acid Supplementation among Pregnant Women at a Tertiary Hospital in Southern Nigeria - , Chioma O. Ozueh; , Justina O. Alegbeleye (Archives of Current Research International, 2022)
Background: Folic acid is an essential water-soluble vitamin that cannot be synthesized in the human body and so its major source is from diet. It plays an important role in embryonic development. Folic acid deficiency in pregnant women results in megaloblastic anaemia, increased risk of preterm delivery and neural tube defects. The assessment of its knowledge is essential in preventing neural tube defects. Aim: The aim of this study was to evaluate the awareness and knowledge of folic acid as a preventive measure for neural tube defects, and their determinants amongst pregnant women at the University of Port Harcourt Teaching Hospital. Materials and Methods: This was a descriptive cross-sectional study conducted among 451 antenatal attendees at the University of Port Harcourt Teaching Hospital from January 1 to March 31, 2020. A structured interviewer-administered questionnaire was used to obtain information from the women after consent was given. Data obtained was collated, entered in a spread sheet, and analyzed using SPSS version 25. Results are expressed in means and percentages. The confidence interval was set at 95% and a p-value of < 0.05 was statistically significant. Chi square test and Pearson’s correlation were used to determine association between knowledge of folic acid and variables. Results: Majority 258 (57.2%) of the women were aged 30-39 years and were mostly nulliparous 122 (27.1%). Over two-third 330 (73.2%) had post-secondary education and almost all 409 (90.7%) of the women were married. Most 375 (83.1%) of the pregnant women were aware of folic acid and its use in peri-conception care. The main source of information was from healthcare workers (54.8%), followed by family and friends (14.6%) and online media (12.0%). Only 169 (37.5%) were aware of the role of folic acid in preventing NTDs. Knowledge about the role of folic acid in the prevention of neural tube defects was significantly associated with younger age, post-secondary education, occupation, and low parity (p value <0.05). Conclusion: Age, educational level, occupation, and parity were significantly predictive of knowledge of folic acid in the prevention of neural tube defects.